Sing after God a New Song. Ritual-musical Appropriations of Psalms in Contemporary Dutch and Flemish culture - Henk Vogel (Yearbook for Ritual and Liturgical Studies)
Summary of PhD Thesis. This thesis was defended on November 28, 2024 at the Protestant Theological University (Utrecht, the Netherlands). Supervisors: prof. dr. Marcel Barnard (Protestant Theological University) and prof. dr. Mirella Klomp (Protestant Theological University). This research was funded by the Stichting Luthers Diakonessenhuis Fonds.